Studi Kasus Nitrogen Dioksida dalam Ruang Bahan Kimia - Kusuma Sari, Mustika; Andriyogana, Ridwan; Zulfah, Nida (Universitas Sarjanawiyata Tamansiswa, 2024)
Indoor air quality is something that describes the indoor air quality in a building suitable for human activity and comfort. The purpose of this research was to determine indoor air quality based on NO2 levels in the air and No2-N levels resulting from dehumidifier absorption. The research was conducted on June 20 2023 and June 27 2023 in the materials room of the environmental quality laboratory faculty of civil engineering and planning (FTSP UII) Yogyakarta. In the morning at 08.00 WIB and in the afternoon at 16.00 WIB with each measurement for 60 minutes. The research method used in this research is quantitative research with data analysis techniques descriptive analysis. In the material room, the nitrogen dioxide (NO2) parameter does not meet the NAV while the NO2-N parameter meets the NAB.